Analisis Kualitas Briket Arang Berdasarkan Komposisi Serbuk Arang Pelepah Kelapa Sawit (Elais guineensis Jacq) dengan Serbuk Arang Pelepah Aren (Arenga pinnata Merr) - Rindayatno; Fathur Rohman; Agus Nur Fahmi (Jurnal Multidisiplin Madani, 2022)
The potential of green energy as a complement and substitute for fossil energy continues to be promoted, one of which is based on biomass. Biomass (plant) based charcoal briquettes can support the fulfillment of energy needs, create jobs, and are relatively low in emissions. The aim of the study was to determine and analyze the quality of charcoal briquettes based on the composition of a mixture of palm oil (Elais guineensis Jacq) and Aren (Arenga pinnata Merr) midrib charcoal powder mixtures. Carbonization is carried out using a furnace with an indirect heating method. Data were analyzed by Completely Randomized Design (CRD) 5 treatments, namely (A) composition of 100% palm oil midrib, (B) 75% palm oil midrib and 25% sugar palm midrib, (C) 50% palm oil midrib and 50% sugar palm midrib, (D) 25% palm oil midrib and 75% sugar palm midrib, and (E) 100% sugar palm midrib. The best quality of charcoal briquettes was obtained from treatment E (100% palm oil midrib) with a density of 0.617 g/cm3, water content 4.174%, compressive strength 92.700 kg/cm2, volatile matter content 36.800%, ash content 6.500%, fixed carbon content 56.700%, and calorific value 5.843 cal/g. Charcoal briquettes with a mixture of charcoal powder 25% palm oil midrib and 75% sugar palm midrib is the best mixture composition with quality characteristics of charcoal briquettes: density 0.574 g/cm3, water content 4.504%, compressive strength  80.451 kg/cm2, volatile matter content 37.400%, ash content 7.800%, fixed carbon 54.800%, and calorific value 5,623 cal/g. Several test results of charcoal briquettes meet the quality reference of charcoal briquettes from P3HH and SNI No. 01-6235-2000.